Carbapenem Resistant Enterobacteriaceae in Africa - Bashar Haruna Gulumbe; Olumide Ajibola (Borneo Journal of Pharmacy, 2020)
Carbapenems are regarded as unique among the β-lactam antibiotics due to their broad spectrum of activity and ability to resist β-lactamase hydrolysis. Carbapenems are the only β-lactam antibiotics with efficacy in severe infections caused by extended-spectrum beta-lactamase (ESBL) producing bacteria. However, recent reports of carbapenem resistance particularly among members of Enterobacteriaceae that are responsible for diseases such as gastrointestinal infections, septicemia, pneumonia, meningitis, peritonitis as well as urinary tract infections, call for concerns. In Africa, the problem of carbapenem-resistant Enterobacteriaceae (CRE) is aggravated by factors such as the high rate of infections, poor diagnostic tools, sub-optimal disease surveillance, and abuse of antibiotics. Besides, the problem of CRE in Africa is understudied. This review distills available literature on the spread of CRE in Africa, CRE genes in circulation, and the need to pay attention to this emerging threat to lives in developing countries.